Responsible innovation as empowering ways of knowing. Issue 1 (2nd January 2020) - Valkenburg, Govert; Mamidipudi, Annapurna; Pandey, Poonam; Bijker, Wiebe E.
ABSTRACT: In pursuit of responsible research and innovation (RRI), emphasis has been on various forms of inclusion in the governance of science, technology and innovation. Given that much of the ideas on inclusion in fact refer to discursive inclusion, it is surprising that little attention has hitherto been paid to what seems foundational to any discursive space: ontologies (theories of being) and epistemologies (theories of knowing), and notably how these relate to inclusion and exclusion. By means of an action-research case study on responsible innovation on biogasification in rural India, we show that one important mechanism of exclusion exists in a dispossession of epistemological agency and the rendering of ontologies as anomalous, even if this is not directly visible as social exclusion. We argue that RRI should adopt as one of its central values the epistemological empowerment of relevant groups.